Transition From Full Mu Opioid Agonists to Buprenorphine in Opioid Dependent Patients—A Critical Review - Soyka, Michael (Frontiers in Pharmacology, 2021)
Methadone, a full opioid agonist, and buprenorphine, a partial agonist, are first-line medications in opioid maintenance treatment. Transition from methadone to buprenorphine may precipitate withdrawal, and no accepted algorithm for this procedure has been developed. Current treatment strategies suggest transfer from methadone to buprenorphine only in patients at low doses of methadone (30-40 mg/day). There are some reports indicating that transition also from higher doses of methadone may be possible. A number of dosing strategies have been proposed to soften withdrawal symptoms including use of other opioids or medications and especially microdosing techniques for buprenorphine. The case series and studies available so far are reviewed.